IMPLEMENTATION OF THE LEAST SQUARE METHOD TO FORECAST CEMENT SALES - Lita Juliana Lita Juliana; Adi Prijuna Lubis; Iin Almeina Lubis (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Background: Frequent shortage of cement stock causes consumer demand to not be fulfilled. Over time, the uncertain demand for each product can cause difficulties in determining the supply of cement brands in the future. Forecasting techniques are very influential on the decision of the owner of UD Timbul Rezeki to determine the amount of inventory that must be provided. Method: Using the Least Square Method which is one method in the form of time series data, which requires past sales data to forecast future sales. Quantitative method is a research method used to examine a particular population or sample, the sampling technique is generally done randomly. Result: The results of the application of the Least Square Method for forecasting cement sales for the September 2022 period at UD Timbul Rezeki got the results of forecasting Garuda cement totaling 439.85 sacks, red and white cement totaling 321.06 sacks, Holcim cement totaling 273.18 sacks, three-wheeling cement totaling 669 ,70 sacks and cement jakarta amounted to 270.23 sacks. Conclusion: This results in a system design that can predict the amount of cement inventory using the Least Square Method at UD Timbul Rezeki, so that the cement management process takes place more effectively and efficiently, because the forecasting process is fast and can help the cement sales forecasting process easily.